A Comparative Study of the Legal Community in “Dongwu” (1915–1952) - MA, Guangxia (Journal of Research for Christianity in China (JRCC), 2025)
The Soochow Law School stands as a monumental achievement in the history of modern legal education in China. It emphasized distinctive teaching approaches in Anglo-American law and comparative law, cultivating a cohort of outstanding legal professionals in the modern era. The formation of the “Soochow” legal community resulted from multiple factors, including characteristics inherent to Soochow University itself, regional influences from Shanghai, and broader national circumstances of the time.
Keywords: Lan Jin, Liu Bomu, Wu Jingxiong, Sheng Zhenwei, Yang Zhaolong